Distinct risk factors of atrial fibrillation in patients with and without coronary artery disease: a cross-sectional analysis of the BOREAS-CAG Registry data. Issue 1 (16th January 2017) - Murakami, Naoto; Tanno, Masaya; Kokubu, Nobuaki; Nishida, Junichi; Nagano, Nobutaka; Ohnishi, Hirofumi; Akasaka, Hiroshi; Miki, Takayuki; Tsuchihashi, Kazufumi; Miura, Tetsuji
Abstract : Objective: Although risk factors of atrial fibrillation (AF) in the general population have been characterised, their impacts on patients with specific diseases are unclear. Our aim was to determine whether risk factors of AF are different in patients with and those without coronary artery disease (CAD). Methods: We enrolled 1871 consecutive patients who underwent coronary angiography for evaluation of symptoms suggestive of CAD in the BOREAS-CAG Registry between August 2014 and January 2015. After exclusion of patients with valvular heart disease or a history of PCI/cardiac surgery, 1150 patients contributed to multivariate logistic regression analysis to identify risk factors of AF. We also retrieved data for 361 consecutive patients with CAD admitted to Sapporo Medical University Hospital between April 2013 and July 2014 and analysed data for 166 patients using the same inclusion and exclusion criteria as those in the BOREAS-CAG Registry. Results: Unexpectedly, CAD was independently associated with the absence of AF. The patients were then divided into a non-CAD group (n=576) and a CAD group (n=574) for further analysis. The brain natriuretic peptide level showed a strong association with AF regardless of the presence or absence of CAD. In the non-CAD group, lack of statin use was independently associated with AF, whereas high serum uric acid level was an independent explanatory variable of AF in the CAD group. The association of AF with uric acid was confirmed in a separate group of patients (n=166) enrolled in the CAD cohort in Sapporo Medical University Hospital. Conclusions: Major risk factors of AF are different in patients with CAD and those without CAD. Patients with CAD are more likely to develop AF when the serum uric acid level is high, whereas no statin administration predicts development of AF in patients without CAD.